Activated Prothrombin Complex Concentrate Versus 4-Factor Prothrombin Complex Concentrate for Vitamin K-Antagonist Reversal*. Issue 6 (June 2018) - Rowe, A. Shaun; Dietrich, Scott K.; Phillips, John W.; Foster, Kaci E.; Canter, Joshua R.
Abstract : Objectives: To compare the international normalized ratio normalization efficacy of activated prothrombin complex concentrates and 4-factor prothrombin complex concentrates and to evaluate the thrombotic complications in patients treated with these products for warfarin-associated hemorrhage. Design: Retrospective, Multicenter Cohort. Setting: Large, Community, Teaching Hospital. Patients: Patients greater than 18 years old and received either activated prothrombin complex concentrate or 4-factor prothrombin complex concentrate for the treatment of warfarin-associated hemorrhage. We excluded those patients who received either agent for an indication other than warfarin-associated hemorrhage, pregnant, had a baseline international normalized ratio of less than 2, received a massive transfusion as defined by hospital protocol, received plasma for treatment of warfarin-associated hemorrhage, or were treated for an acute warfarin ingestion. Interventions: Patients in the activated prothrombin complex concentrate group (enrolled from one hospital) with an international normalized ratio of less than 5 received 500 IU and those with an international normalized ratio greater than 5 received 1, 000 IU. Patients in the 4-factor prothrombin complex concentrate (enrolled from a separate hospital) group received the Food and Drug Administration approved dosing algorithm. Measurements and Main Results: A total of 158 patients were included in the final analysis (activated prothrombin complex concentrate = 118; 4-factor prothrombin complex concentrate = 40). Those in the 4-factor prothrombin complex concentrate group had a higher pretreatment international normalized ratio (2.7 ± 1.8 vs 3.5 ± 2.9; p = 0.0164). However, the posttreatment international normalized ratio was similar between the groups. In addition, even when controlling for differences in the pretreatment international normalized ratio, there was no difference in the ability to achieve a posttreatment international normalized ratio of less than 1.4 (odds ratio, 0.753 [95% CI, 0.637–0.890]; p = 0.0009). Those in the activated prothrombin complex concentrate group did have higher odds of achieving a posttreatment international normalized ratio of less than 1.2 (odds ratio, 3.23 [95% CI, 1.34–7.81]; p = 0.0088). There was only one posttreatment thrombotic complication reported. Conclusions: A low, fixed dose of activated prothrombin complex concentrate was as effective as standard dose 4-factor prothrombin complex concentrate for normalization of international normalized ratio. In addition, we did not see an increase in thrombotic events.